Geoscience of Climate and Energy 8. Climate Models: Are They Compatible with Geological Constraints on Earth System Processes? - Peltier, W. Richard (Geoscience Canada, 2010)
Models of the global warming process are obliged to include many important small-scale processes that cannot be explicitly represented, given the low spatial and temporal resolution at which the models can be integrated. As the parameterizations of these processes, in terms of the resolved scale fields, must be tuned to permit them to enable the models to fit climate observations from the instrumental era, it is an issue as to whether such models remain robust when they are applied to the prediction of future warming trends. Geological inferences of past climate conditions provide a means by which the robustness of the models may be assessed. In this paper, two examples of such tests are described, both of which demonstrate that a state-of-the-art model is able to accurately simulate past conditions that differ radically from modern. SOMMAIRE Les modèles de processus de réchauffement climatique de la planète doivent intégrer de nombreux et importants processus à petite échelle, lesquels ne peuvent être représentés de façon explicite, étant donné la faible résolution spatiale et temporelle des modèles climatiques. Comme le paramétrage de ces processus, à leur échelle propre, doit être ajusté de manière à permettre aux modèles de correspondre à l'observation du climat de l'aire instrumentale, il faut savoir si de tels modèles peuvent demeurer robustes lorsqu’ils sont utilisés pour prévoir les tendances de réchauffement à venir. Or, les inférences climatiques passées déduites de situations géologiques constituent un moyen de tester la robustesse des modèles. Dans le présent article, deux exemples de ces tests sont décrits, et ceux-ci montrent que les modèles actuels sont capables de reproduire avec précision des conditions climatiques anciennes très différentes des conditions actuelles.